Narrativas de formadores de professores dos CEFAPROs de Mato Grosso : políticas e práticas de formação continuada - Camargo, Rosimeire Dias de (2021)
This study is guided by the research line School Organization, Formation and Pedagogical Practices of the Post Graduation Program on Education at the Federal University of Mato Grosso. It has been constructed according to the qualitative perspective of research in the field of Education, which, methodological design is based on the narrative research, assumed by the researchers D. Jean Clandinin, F. Michael Connelly and their collaborators, who considered it as a method and phenomenon of study. The authors were inspired by Dewey’s considerations who believes that the philosophical view of experience as a key concept of narrative investigation. Guided by this ongoing movement which, problematized the Continuing Eucation in Mato Grosso based on the experiences lived on this context, this research aimed at understanding the conceptions of formation and formation practices that reside in the official documents used in the Continuing Education, as well as, it wants to discloses how the educators formers resignify these concepts in their professional performance. The ongoing research movement counted on nine research trainers, who under my guidance had been investigating at seven CEFAPROs. The development of this investigative process was based on narrative research which embraces Dewey's theoretical assumptions to situate the thoughts as reflexive acts and the understanding of experience as a flow of human life. The theoretical contributions came from the studies of educators formation, training and professional development by Nóvoa, Garcia and Monteiro, among other researchers. The field texts were gathered by oral and written narratives (digital/audiovisual) encompassed on the narrative interviews, conversations, autobiographical concerning the personal and professional trajectory and official narratives present in the document of the Educators Continuing Education Policies in the state of Mato Grosso. The structure of meanings of lived and narrated experiences, which I name resounding narrative threads, ocurred of the resonances present in the different narratives of the researched formers in which composition comprised the professional identification, as well as, the challenges and tension lives in the daily life of the continuing formation. In this sense, the composition of the meanings concerning the lived and narrated experiences, beyond of the findings, it has highlighted to the importance of the CEFAPRO, as a public space of formation, as well as, it has exposed the fragility present in the scope of the oficial narratives concerning the continuos teachers’ formation in Mato Grosso which dynamics needs to strengthen this formative movement in the theoretical and practical fields. Consequently, following the foundations of the narrative research, I comprehend that the investigation movement has not been limited to narrating the inconsistencies present in the investigated context, nonetheless they offers other understandings and reflections that may support to improve the contemporary perspective.